Politics of Education in Developing Countries From Schooling to Learning - Hickey, Sam; Hossain, Naomi (Oxford University Press, 2019)
This book examines the politics of the learning crisis in the global South, where learning outcomes have stagnated or worsened, despite progress towards Universal Primary Education since the 1990s. Comparative analysis of education reform in Bangladesh, Cambodia, Ghana, Rwanda, South Africa, and Uganda highlights systemic failure on the frontline of education service delivery, driven by deeper crises of policymaking and implementation: few governments try to raise educational standards with any conviction, and education bureaucracies are unable to deliver even those learning reforms that get through the policy process. Introductory chapters develop a theoretical framework within which to examine the critical features of the politics of education. Case study chapters demonstrate that political settlements, or the balance of power between contending social groups, shape the extent to which elites commit to adopting and implementing reforms aimed at improving learning outcomes, and the nature this influence takes. Informal politics and power relations can generate incentives that undermine rather than support elite commitment to development, politicizing the provision of education. Tracing reform processes from their policy origins down to the frontline, it seems that successful schools emerged as localized solutions to specific solutions, often against the grain of dysfunctional sectoral arrangements and the national-level political settlement, but with local political backing. The book concludes with discussion of the need for more politically attuned approaches that focus on building coalitions for change and supporting 'best-fit' types of problem-solving fixes, rather than calling for systemic change.